The Effectiveness of the Effect of Holding Time on the Toughness and Macro Structure of Low Carbon Steel Due to Carburizing Pack of Pine Charcoal - Nitha, Nitha; Sampelawang, Petrus; Ba’dung, Henry Sofianto (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This study aims to determine the effectiveness of holding time variation of fir charcoal with oil cooling media SAE 20 on the toughness of low carbon steel ST 37 due to the pack carburizing process. This research method, namely impact test, and macrostructure. In the pack carburizing process using fir charcoal and SAE 20 oil cooling media on the toughness and macrostructure of low carbon steel ST 37. The holding time used is 1,2,3,4 and 5 hours. After the carburizing process, a toughness test and macrostructure observation were conducted. From the results of the toughness test obtained the value of each: 17.513 kJ/mm2 at a holding time of 1 hour, 11.920 kJ/mm2 at a holding time of 2 hours, 13.196 kJ/mm2 at a holding time of 3 hours, 7. 917 kJ/mm2 at a holding time of 4 hour, and 3.081 kJ/mm2. Then for macro photo observations greatly, it can be seen that holding time variations greatly affect the holding time, the more tenuous the steel structure